Strategi Kepemimpinan Kepala Roudlotul Athfal Dalam Program Pengenalan Tahfidzul Qur’an Di RA Waqiah Desa Pekukuhan Kecamatan Mojosari Kabupaten Mojokerto - Dita Sulfiana; Sigit Priyo Sembodo (CV. ITTC INDONESIA, 2026)
Leadership strategy refers to a leader’s ability to design, implement, and direct programs effectively to achieve educational institutional goals. This study aims to describe the leadership strategies of the head of the madrasa in implementing the Tahfidzul Qur’an Program using the murrotal and muroja’ah methods at RA Waqiah Pekukuhan Mojosari. The Tahfidzul Qur’an program is designed to strengthen, reinforce, and preserve students’ Qur’anic memorization from an early age in a sustainable manner. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the leadership strategy is implemented through three main stages: planning, implementation, and evaluation. In the planning stage, the head of the madrasa collaborates with the vice principal for curriculum to prepare a Daily Activity Plan (RKH), which includes teacher schedules and memorization materials such as selected surahs, daily prayers, and hadiths. The implementation stage is carried out through collective murrotal and muroja’ah activities involving all KB and RA students under teacher supervision. The evaluation stage is conducted through daily observation-based assessments using anecdotal records and checklists, which are reported weekly to parents. The program has proven effective in enhancing students’ social interaction and strengthening their Qur’anic memorization, particularly Surah Yasin, Al-Waqi’ah, short surahs in Juz 30, selected hadiths, and daily prayers.